A FUZZY- AHP APPROACH TO EVALUATE THE CRITERIA OF THIRD -PARTY LOGISTICS (3PL) SERVICE PROVIDER - Jovčić, Stefan; Průša, Petr; Samson, Josef; Lazarević, Dragan (University of Belgrade, 2019)
This paper deals with the criteria that should be taken into consideration when making a decision about Third-Party Logistics (3PL) service providers and their evaluation. Not all the criteria is equally important, so it is necessary to evaluate them in order to determine the priority and help the company to make a decision. The criteria for 3PL assessment were defined by consulting several experts in the field of logistics. It is very important to analyze and evaluate 3PL providers because there are a very large number of providers in the market and for the company it is very important to choose the right one, based on the relevant criteria. The methodology used for evaluation of the criteria is based on Fuzzy-AHP (Analytic Hierarchy Process) approach. This approach combines the Saaty’s scale (which gives the value of most importance in the statements-criteria) and fuzzy logic (which deals with the linguistic statements). The main result of the paper is to rank the criteria by importance and direct it for the further research in the field of 3PL.
FUZZY- AHP přístup k hodnocení kritérii TŘETÍ -PARTY logistika (3PL) výběru poskytovatele služeb
Keywords: Third-Party Logistics (3PL) Service Provider; Fuzzy-AHP approach; 3PL evaluation criteria; Poskytovatel služeb třetí strany pro logistiku (3PL); Fuzzy-AHP přístup; 3PL hodnotící kritéria